The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3389/fendo.2020.522340
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Overexpression of microRNA-216a-3p Accelerates the Inflammatory Response in Cardiomyocytes in Type 2 Diabetes Mellitus by Targeting IFN-α2

Abstract: Background: Type 2 diabetes mellitus (T2DM) is a chronic, hyperglycemia-associated, metabolic disorder. Heart disease is a major complication of T2DM. The present study aimed to explore the effects of miR-216a-3p on cardiomyocyte proliferation, apoptosis, and inflammation in T2DM through the Toll-like receptor (TLR) pathway involving interferon-α2 (IFN-α2) mediation.Methods: T2DM was induced in rats by a high-fat diet, in combination with an intraperitoneal injection of low-dose streptozotocin. ELISAs were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…DR, as one of the most severe microvascular complications of T2DM, has been extensively investigated based on the animal models, among which the co-induction of HFD and STZ injection has been the mainstream method to construct the T2DM rat models. [18,19] In this study, miR-93-5p was found to be upregulated in the retina of T2DM models induced by HFD and STZ injection, which was similar in DR patients and high glucose-induced human RPE and ARPE-19 cells in the previous study. [31] The work of Mammadzada P et al indicated that miR-93 was upregulated in proliferative diabetic retinopathy (PDR) vitreous, particularly the vitreous from post-recurrent vitreous hemorrhage (RVH) patients [10].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…DR, as one of the most severe microvascular complications of T2DM, has been extensively investigated based on the animal models, among which the co-induction of HFD and STZ injection has been the mainstream method to construct the T2DM rat models. [18,19] In this study, miR-93-5p was found to be upregulated in the retina of T2DM models induced by HFD and STZ injection, which was similar in DR patients and high glucose-induced human RPE and ARPE-19 cells in the previous study. [31] The work of Mammadzada P et al indicated that miR-93 was upregulated in proliferative diabetic retinopathy (PDR) vitreous, particularly the vitreous from post-recurrent vitreous hemorrhage (RVH) patients [10].…”
Section: Discussionsupporting
confidence: 73%
“…Of note, Sirt1 down-regulation has been reported in the retinas of diabetic mice [15][16][17]. In this context, rats were fed with high-fat diet (HFD) and injected with streptozotocin (STZ) to construct the T2DM models [18,19], followed by the intravitreal injection of antagomir NC (negative control), miR-93-5p antagomir, miR-93-5p agomir and/or recombinant Sirt1, and this model could provide the opportunity to investigate the effect of miR-93-5p-targeted Sirt1 on the retinal damage of STZ-induced T2DM rats.…”
Section: Introductionmentioning
confidence: 99%